Rasionalisasi Sakit dan Penyakit dalam Konstelasi Budaya Minangkabau (Kajian Etnomedisin di Agam dan Tanah Datar) - Yunarti Yunarti; Nurainas Nurainas; Yulkardi Yulkardi; Fitria Ramona (Antropologi Indonesia, 2014)
A medical system whether traditional or modern, is a long chain of processes of humanstrategy for adapting to their ecological bio-cultural environment. Naturally humans developtheir biological ability to sustain their kind and develop many adaptation strategies, creatingmedical systems, behavior, and belief sbased on culture as a natural response to the treat ofillness and disease, even though the result of certain behavior does not guarantee the healingof such illness and disease (Dunn in Foster-Anderson, 1986; p.41). under that circumstances,Minangkabau medical systems are seen as a result of a bio-eco-culturally adapting process.Local Etiology of the disease source is closely related to the logic of its healing. Cosmologicalviews influence public knowledge about the concepts of health, illness, disease, and healingmethods. The definition of health and illness is determined by culture, custom, or traditionand it is not always in agreement with the conditions defined by medical science.Keywords: rationalization of illness and disease; constellation of Minangkabau culture;ethnomedicine